79. Multichannel EMG in orthostatic tremor. Issue 1 (January 2015) - La Gioia, S.; Frigeni, B.; Conte, P.; Viscardi, M.; Conti, M.; Foresti, C.
<x xml:space="preserve">Abstract</x> Essential tremor (ET) is a clinical syndrome characterized by an action tremor in the upper limbs and its electromyography (EMG) pattern is represented by 8–12 Hz bursts. Orthostatic tremor (OT) is a rare syndrome characterized by unsteadiness on standing due to a high-frequency tremor involving the legs during isometric contraction. Typically, the symptoms rapidly improve on sitting or walking. OT has a distinctive EMG frequency of 13–18 Hz which discriminates it from ET, cerebellar tremor and myoclonus. Polygraphic recording of fast tremor of legs confirms OT diagnosis. We evaluated the EMG pattern of OT in a 64-year-old man with a progressive tremor of quadriceps and gluteus muscles in the standing position over a period of six months. It rapidly vanished during walking or sitting and no such movement was evident in the upper limbs. Blood tests, brain and spinal MRI, and evoked potentials were normal. Multichannel EMG of the lower limbs showed discharges of muscle activity at 15 Hz during isometric contraction, while on supine posture they were not recordable in the same muscles unless put into a state of isometric contraction, so obtaining discharges of lower frequency (9 Hz). These results confirmed OT diagnosis.